Development of Optical Biosensor to Determine Benzoic Acid Concentration Based on Its Inhibitive Effect on Tyrosinase Enzyme - Hamzah, Hairul Hisham (2010)
An optical biosensor using phenol biosensor for the determination of benzoic acid based on inhibitive effect of benzoic acid on tyrosinase enzyme has been developed in this study. Two methods were developed which were based on in-solution tyrosinase and immobilized tyrosinase. Tyrosinase enzyme, phenol and 3-methyl-2-benzothiazolinone hydrazone (MBTH) were used as reagents for determination of benzoic acid. In-solution and immobilized tyrosinase as sensing element were successfully applied for the determination of benzoic acid. In the detection of benzoic acid based on in-solution tyrosinase, the solution changed its color from dark maroon to light maroon depending on the concentration of benzoic acid, due to the inhibition of tyrosinase reaction by benzoic acid with response time of thirty minutes. The absorbance of products as the output of enzymatic reaction was detected by using uv-visible spectrophotometer with maximum absorbance at 504 nm. The biosensor demonstrated optimum activity at pH 7. The relative standard deviation (RSD) of the reproducibility of this method was very good with RSD value of 1.91 %. The dynamic range of benzoic acid concentration was found to be between 50 ppm to 700 ppm with the detection limit (LOD) of 0.19 ppm. The kinetic parameters Michaelis-Menten constant (KM) and maximum absorbance (Amax) in the absence and presence of benzoic acid showed the inhibition of benzoic acid on tyrosinase activity is competitive inhibitor with the inhibition constant (Ki) 90.9 ppm. Test strip for detection of benzoic acid was developed by immobilizing tyrosinase, phenol and MBTH into filter paper using polystyrene as a polymeric support. The sensing scheme was based on the decreasing intensity of maroon color of test strip when dipped into benzoic acid solution. The test strip was characterized using optical fiber reflectance spectrometer (OFRS) and the result showed the test strip had a maximum reflectance at 375.65 nm. The optimum response of biosensor was achieved at pH 7. A linear response of the biosensor was obtained in the benzoic acid concentration range of 50 ppm to 700 ppm with LOD of 0.28 ppm. The reproducibility of the biosensor was good with calculated RSD of 0.47 %. The kinetic analyses showed that the inhibition of benzoic acid on tyrosinase activity was reversible and competitive inhibition with Ki of 52.9 ppm. The activity of the developed test strip was fairly sustained during for 20 days when stored at 3° C. The results obtained from both methods developed in this study were compared with the established method of high performance liquid chromatography (HPLC). Excellent agreement was obtained between the developed and the HPLC methods.